Olaratumab for the treatment of soft-tissue sarcoma. (October 2017) - Pender, Alexandra; Jones, Robin L
The outcome for patients with unresectable/metastatic soft tissue sarcoma remains poor with few treatment options. In the first line setting, a number of randomized trials have shown no difference in overall survival between combination anthracycline schedules and single agent doxorubicin. A Phase Ib/randomized Phase II trial of doxorubicin with or without the monoclonal antibody to PDGFR-α, olaratumab, demonstrated a significant difference in median overall survival in favor of the olaratumab arm. The results of this trial led to approval of olaratumab in combination with doxorubicin in adult anthracycline-naive unresectable soft tissue sarcoma. In this review, we describe some of the preclinical and early clinical data of olaratumab in sarcomas, the Phase Ib/II trial and ongoing trials with olaratumab in sarcomas.